(untitled) - Buber, Renate (New York, N.Y., 2003)
Qualitative research methodologies are gaining more and more acceptance. This book deals with the application of qualitative methods to marketing management research. It explains different ways of making and analyzing data with qualitative tools, and it describes the generation of results working for researchers as well as for practitioners in marketing management. Teachers and students in marketing and research methodology, as well as researchers and practitioners in marketing management will find useful material on research methods and case study research.
Keywords: Marketing,Qualitative research; Management,Research